The Role of Self-Concepts on The Relationship Between Fashion Brand Experience and Repurchase Intention - Yang, Byunghwa (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The current study aimed to investigate the relationship between brand experiences and repurchase intentions through self-concept constructs, including self-congruence and self-esteem. Methods/Statistical analysis: Three hundred and sixty-two Korean undergraduate students participated in this study. Participants were recruited from online student community in a university and completed the survey questionnaire. Survey items were adopted from existing literature. The study used path analysis to examine how research variables related, and convergent validity and discriminant validity for these variables were confirmed. Findings: The results of the structural model showed direct effects of brand experiences on self-congruence were supported. These effects include sensory, behavioral and intellectual experiences on self-congruence. However, the direct effect of brand experiences on self-esteem was only supported in the behavioral dimension. Also, self- congruence had a direct effect on self-esteem and an indirect effect on repurchase intention through self-esteem. In addition, self-esteem had a direct effect on repurchase intention and a mediating effect on the linkage between brand experience and repurchase intention. Similarly, self-congruence had a mediating effect on the connection between brand experience and repurchase intention, supporting the dual mediation model. Improvements/Applications: Future research may compare the effectiveness of luxury and non-luxury brands. Brand managers may develop experiential strategies that extend beyond mere sensory experiences via marketing channel mix.